Enriched environment at work: Disassociated from stress and burnout. - Rodriguez, Francisca S.; Luck, Tobias; Riedel-Heller, Steffi G. (Work, 2018)
BACKGROUND: Enriched environment at work (EEW), in terms of high mental demands at work, may be of great relevance for preventative efforts against cognitive decline and dementia as previous studies have shown. Yet, there is the concern that high EEW mental demands may accelerate stress and cause burnout. OBJECTIVE: The aim of our study was to investigate how EEW mental demands are related to stress and burnout. METHOD: A convenience sample of employees in the city area of Leipzig, Germany, was asked to fill out the Copenhagen Burnout Inventory and indicate for each EEW mental demand the level experienced, demandingness, and stressfulness. RESULTS: Multivariate linear regression and structural equation modelling suggested that only some EEW mental demands were perceived as stressful when the level of the respective EEW mental demand was high. Higher stressfulness was associated with burnout symptoms – however, high levels of EEW mental demands were not significantly associated with burnout (neither directly nor indirectly). CONCLUSIONS: Our findings implied that subjectively perceived stressfulness seems to be a more relevant aspect than the actual level of the demand itself. However, further studies are necessary to validate our findings.